Genetic analysis of typical wet-type age-related macular degeneration and polypoidal choroidal vasculopathy in Japanese population - Asako Goto; Masakazu Akahori; H. Okamoto; M. Minami; N. Terauchi; Y. Haruhata; Minoru Obazawa; Toru Noda; Miki Honda; Atsushi Mizota; Minoru Tanaka; Takaaki Hayashi; et al. (2009)
Age-related macular degeneration (AMD) is a common cause of blindness in the elderly. Caucasian patients are predominantly affected by the dry form of AMD, whereas Japanese patients have predominantly the wet form of AMD and/or polypoidal choroidal vasculopathy (PCV). Although genetic association in the 10q26 (ARMS2/HTRA1) region has been established in many ethnic groups for dry-type AMD, typical wet-type AMD, and PCV, the contribution of the 1q32 (CFH) region seem to differ among these groups. Here we show a single nucleotide polymorphism (SNP) in the ARMS2/HTRA1 locus is associated in the whole genome for Japanese typical wet-type AMD (rs10490924: p = 4.1 x 10(-4), OR = 4.16) and PCV (rs10490924: p = 3.7 x 10(-8), OR = 2.72) followed by CFH (rs800292: p = 7.4 x 10(-5), OR = 2.08; p = 2.6 x 10(-4), OR = 2.00), which differs from previous studies in Caucasian populations. Moreover, a SNP (rs2241394) in complement component C3 gene showed significant association with PCV (p = 2.5 x 10(-3), OR = 3.47). We conclude that dry-type AMD, typical wet-type AMD, and PCV have both common and distinct genetic risks that become apparent when comparing Japanese versus Caucasian populations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12177-009-9047-1) contains supplementary material, which is available to authorized users.